PENGARUH ADOPSI XBRL DAN UKURAN PERUSAHAAN TERHADAP RISIKO INFORMASI SEBAGAI FAKTOR PENENTU PENGAMBILAN KEPUTUSAN INVESTASI - Siti Urmilah Sasmita (2021)
The purpose of this study is to examine the effect of XBRL adoption and company size on information risk as a determining factor in investment decision making. In this study, XBRL adoption is measured using dummy variables, company size is measured using the natural logarithm of total assets, and information risk as a determining factor for investment decision making is measured using the Event Return Volatility (ERV). The population in this study were all companies listed on the Indonesia Stock Exchange for the period 2013 - 2018 and The samples in this study are all banking companies listed on the Indonesia Stock Exchange. The sample was selected by purposive sampling method and collected 141 data samples. Hypothesis testing in this test uses Multiple Linear Regression Analysis with the SPSS version 25 program and a significance level of 5% (0.05). The results of the test show that: 1) XBRL adoption has a significant negative effect on information risk as a determining factor in investment decision making; 2) company size has no significant effect on information risk as a determining factor in investment decision making.